2021
DOI: 10.3324/haematol.2020.266320
|View full text |Cite
|
Sign up to set email alerts
|

An international retrospective study for tolerability of 6-mercaptopurine on NUDT15 bi-allelic variants in children with acute lymphoblastic leukemia

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…14 In one case of homozygous *5 (*5/*5) in the recent study, the patient did not show severe intolerance. 11 However, patients with compound heterozygous variants (*2/*5 or *3/*5) showed strong intolerance to 6-MP. 11,14 Correspondingly, in the analysis, patients with *1/*5 showed a slightly lower NUDT15 expression level than WT and patients with compound heterozygous variants (*2/*5 or *3/*5) showed extremely low expression levels of NUDT15.…”
Section: Sionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 In one case of homozygous *5 (*5/*5) in the recent study, the patient did not show severe intolerance. 11 However, patients with compound heterozygous variants (*2/*5 or *3/*5) showed strong intolerance to 6-MP. 11,14 Correspondingly, in the analysis, patients with *1/*5 showed a slightly lower NUDT15 expression level than WT and patients with compound heterozygous variants (*2/*5 or *3/*5) showed extremely low expression levels of NUDT15.…”
Section: Sionmentioning
confidence: 99%
“…In a recent international retrospective study on NUDT15, patients with homozygous and biallelic no-function alleles showed prolonged intolerance to 6-MP and excessive disruption of treatment. 11 Previous data showed that high levels of DNAincorporated thioguanine (DNA-TG) in white blood cells (WBCs) in patients with loss-of-function NUDT15 variants was the pharmacological basis of their 6-MP intolerance. 8,12,13 Studies in laboratory model systems suggest that NUD15 variants, particularly p.R139C, result in unstable proteins and thus reduced enzymatic activity.…”
Section: Introductionmentioning
confidence: 99%
“…In 6-MP treatment, patients with bi-allelic variants experienced severe bone marrow suppression and required the discontinuation or reduction of significant doses. We recently evaluated the association between 6-MP intolerability and clinical characteristics in 37 children with ALL bearing NUDT15 bi-allelic variants in an Asian international collaboration retrospective study [ 14 ]. Among those with NUDT15 bi-allelic variants, more than 90% of the patients had a WBC count of <2000/mm 3 or a neutrophil count of <1000/mm 3 .…”
Section: Nudt15 Variants and Toxicities In Thiopurine Metabolismmentioning
confidence: 99%
“…We further demonstrated that adjusting the initial 6-MP dose is important to prevent the discontinuation of treatment and to allow the continuation of maintenance therapy, based on the NUDT15 genotype. In patients with NUDT15 bi-allelic variant, those who received an initial 6-MP dose of less than 10 mg/m 2 experienced a shorter duration of therapy interruption than those who received more than 10 mg/m 2 in the first 8 weeks (median range, 0 vs. 16 days) [ 14 ]. Based on the guideline of the Clinical Pharmacogenetics Implementation Consortium (CPIC), an initial 6-MP dose of 10 mg/m 2 is recommended for patients with NUDT15 poor metabolizer diplotypes ( *2/*2 , *2/*3 , and *3/*3 ) ( Table 2 ) [ 6 ].…”
Section: Nudt15 Variants and Toxicities In Thiopurine Metabolismmentioning
confidence: 99%
See 1 more Smart Citation